The Concept of Righteous Leadership: King Pṛthu in the Śrīmad Bhāgavata Mahāpurāṇa - Pokhrel, Mohan Kumar (JODEM: Journal of Language and Literature, 2025)
This paper explores how King Pṛthu, the first anointed king in the Paurāṇic tradition, emerges as a paradigmatic figure of ideal kingship whose leadership is legitimized not merely by birth but by divine sanction and personal merit. Through a textual analysis of Canto Four, the study highlights Pṛthu’s multifaceted role-as a protector of the people, a restorer of dharma, a spiritual seeker, and a selfless ruler who prioritizes the well-being of his subjects above personal gain. The major objectives of this study are to identify the defining characteristics of righteous leadership as exemplified by King Pṛthu in the Śrīmad Bhāgavata Mahāpurāṇa; to examine how the text constructs King Pṛthu as an ideal model of dhārmic kingship, integrating spiritual, ethical, and political dimensions; and to explicate the contemporary relevance of King Pṛthu’s leadership model in addressing present-day political and ecological challenges. The researcher uses Max Weber’s sociological theory of authority for the interpretation of the text. The theorist corroborates how moral legitimacy is constructed in the narrative-not through coercive power or legal structures, but through personal virtue, divine approval, and service to the people. The main conclusion drawn from this investigation is that the story of King Pṛthu in the Śrīmad Bhāgavata Mahāpurāṇa underscores that righteous leadership is defined by selfless duty, moral integrity, and the welfare of all beings.